Inhibition of the Immunoproteasome Subunit LMP7 Ameliorates Cerebral White Matter Demyelination Possibly via TGFβ/Smad Signaling. (12th October 2021) - Chen, Xingyong; Yao, Nannan; Lin, Zejing; Wang, Yinzhou
Abstract : Objectives . Chronic cerebral hypoperfusion induces white matter ischemic injury and cognitive impairment, whereas the mechanism remains unclear. Immunoproteasomes have been implicated in the pathogenesis of acute ischemia stroke and multiple sclerosis. However, the expression and role of immunoproteasomes in the brain of chronic cerebral hypoperfusion remain to be clarified. Methods . Chronic white matter ischemic injury mice models were induced by bilateral carotid artery stenosis (BCAS). A selective immunoproteasome subunit low-molecular-mass peptide-7 (LMP7) inhibitor PR957 was administered to mice. Cognitive function, white matter integrity, and potential pathways were assessed after BCAS. Results . The present study found that chronic cerebral hypoperfusion following BCAS induced cerebral white matter demyelination and cognitive impairment, accompanied with elevated expression of the immunoproteasomes LMP2 and LMP7, activation of astrocytes and microglia, and increased production of inflammatory cytokines (e.g., interleukin-1 β (IL-1 β ), tumor necrosis factor- α (TNF- α ), IL-10, transforming growth factor- β 1 (TGF β 1), and insulin-like growth factor-1 (IGF-1)). However, inhibition of LMP7 with the specific proteasome inhibitor PR957 significantly mitigated the histological damage of the white matter, suppressed inflammatory response, and paralleled by an improvement of cognitive function. Furthermore, treatment of PR957 significantly upregulated the level of TGF β 1, the total expression level, and the phosphorylation level of Smad2/3 and promoted brain remyelination. Surprisingly, PR957 alone had no effects on the neuroinflammation response and the activation of TGF β /Smad signaling in the sham-operated (BCAS-nonoperated) mice. Conclusions . The possible mechanism underlying this was attributed to that the immunoproteasome regulates TGF β /Smad signaling-mediated neuroinflammation and oligodendrocyte remyelination.